An evaluation of investment and investment decision-making in the construction industry in South Africa - Heckroodt, Christo (Acta Structilia, 1998)
It seems out of a research survey carried out in South Africa. as well as the general stand of the civil engineering and construction industries over the past few years. that economical and political factors have a far greater influence on the growth of the industry than internal organisational factors. The risk associated with projects. seen within the broad spectrum of other internal and external risk factors. seems to be the biggest concern of investors and developers. Financing construction projects is the second highest factor. and can be of critical importance. The view should always be to improve the cost-effectiveness of the decision of how and what and when to invest. It is evident that the quantity surveyor and/or cost engineer has an important role to play in this regard.